Parenting methods and their impact on children: An applied study on the Emirate of Sharjah - Albah, Jamal; Alothman, Hussain (Al-Adab Journal, 2023)
The study aimed at identifying parental education methods and their impact on children - the Emirate of Sharjah. To achieve the study’s objective, the researcher used the social survey curriculum to fit it into the subject of the study. The researcher designed the questionnaire as a tool for gathering information and consisted of (24) phrases and applied the questionnaire to a sample based on (83.( One of the most important findings of the study was the erroneous methods, namely, the placement of family problems between parents before the children, which came at a high rate of 77.11%. - The results of the study showed sound methods, avoiding excessive cruelty whether in treatment, or in harsh language directed at children, which came with a high rate of 74.10%. - The results of the study revealed the focus on the development of children’s skills and the development of their personality, which came with a high rate of 90.3%. The study concluded with a series of recommendations, including: Fostering children’s positive behaviour through the use of sound methods of education that contribute to the development of their personality, trust and a sense of parental acceptance.